Fashion writing and criticism : history, theory, practice - McNeil, Peter; Miller, Sanda (London, UK ; Bloomsbury, 2014)
"Fashion Writing and Criticism provides students with the tools to critique fashion with skill and style. Explaining the history and theory of criticism, this innovative text demonstrates how the tradition of criticism has developed and how this knowledge can be applied to fashion, enabling students to acquire the methods and proper vocabulary to be active critics themselves. Integrating history and theory, this innovative book explains the development of fashion writing, the theoretical basis on which it sits, and how it might be improved and applied. Through concise snapshot case studies, top international scholars McNeil and Miller analyse fashion excerpts in relation to philosophical ideas and situate them within historical contexts. Case studies include classic examples of fashion writing, such as Diana Vreeland at Harper's Bazaar and Richard Martin on Karl Lagerfeld, as well as contemporary examples such as Suzy Menkes and the blogger Tavi.Accessibly written, Fashion Writing and Criticism enables readers to understand, assess and make value judgments about the fascinating and changeable field of fashion. It is an invaluable text for students and researchers alike, studying fashion, journalism, history and media studies"--
Machine generated contents note: -- AcknowledgementsList of illustrationsPart 1 What is Criticism?Chapter 1 IntroductionChapter 2 Aristotle and the origins of criticismChapter 3 Talking in private: the Academies and the SalonsChapter 4 Understanding Taste: The Critic as Qualified ObserverChapter 5 Charles Baudelaire: the Beginning of Fashion Criticism; The Art Critic of the Salons Chapter 6 Oscar Wilde and the apostles of aestheticism Part 2 Reporting Fashion: OverviewSnapshotsFashion and morality: Leo Tolstoy's What is Art?Paul Poiret: 'sultan of fashion' -- from tradition to innovationDiana Vreeland: 'Why Don't you?' -- the invention of the fashion editorChristian Dior: the 'New Look' and reporting by Carmel SnowYves Saint Laurent -- a 1970s analysis of 'The couturier and his brand'What is fashion irony? Mild sarcasm or feigning ignorance?Reporting on the Japanese revolution in ParisRichard Martin as essayist: Karl Lagerfeld reworks ChanelBeing critical about 'deconstruction': theoretical approach or 'le destroy'?What is a reviewer? -- and how can we recognise one?What gives Suzy Menkes the status of professional critic?ACNE Paper: the beauty of print, the splendour of the pageHow to be a 'critical' blogger: Moving beyond the PR ReleaseConclusion: where do we go from here?BibliographyIndex
Includes bibliographical references and index
Keywords: Fashion writing